Characteristics and Factors Associated With Intimate Partner Violence–Related Homicide Post-Release From Jail or Prison. Issue 21 (November 2021) - Fraga Rizo, Cynthia; Mennicke, Annelise; Van Deinse, Tonya
Intimate partner violence (IPV) victimization and perpetration are common experiences among incarcerated people. Despite knowledge regarding the challenges of re-integrating post-release from jail or prison, including an increased risk of homicide victimization, there is a dearth of research focused on IPV-related homicides post-release from a correctional facility. To address this gap, the current study used 2003-2015 data from the National Violent Death Reporting System from 27 states to examine the characteristics and circumstances surrounding IPV-related homicides soon after the homicide victim was released from jail or prison. Of the 126 post-release homicides, 13.5% were related to IPV. Post-release homicides involving either a female victim or perpetrator were more likely to be IPV-related. In the case of many of the IPV-related homicides, there was evidence of prior IPV as well as potential bystanders (including formal and informal supports) who were aware of the risk for IPV escalation and possible lethality. Compared with non-IPV post-release homicides, those related to IPV were more likely to occur in the victim's home, have been immediately preceded by a physical fight, and have occurred by means other than firearm. These findings highlight the importance of enhancing the capacity of correctional facilities and community-based services to assess for and respond to risk of IPV and IPV-related lethality for individuals leaving correctional institutions.